The Galactic warp revealed by Gaia DR2 kinematics. (13th August 2018) - Poggio, E; Drimmel, R; Lattanzi, M G; Smart, R L; Spagna, A; Andrae, R; Bailer-Jones, C A L; Fouesneau, M; Antoja, T; Babusiaux, C; Evans, D W; Figueras, F; et al.
ABSTRACT: Using Gaia DR2  astrometry, we map the kinematic signature of the Galactic stellar warp out to a distance of 7 kpc from the Sun. Combining Gaia DR2  and 2-Micron All Sky Survey photometry, we identify, via a probabilistic approach, $599 \, 494$ upper main sequence (UMS) stars and $12\, 616\, 068$ giants without the need for individual extinction estimates. The spatial distribution of the UMS stars clearly shows segments of the nearest spiral arms. The large-scale kinematics of both the UMS and giant populations show a clear signature of the warp of the Milky Way, apparent as a gradient of 5–6 km s −1 in the vertical velocities from 8 to 14 kpc in Galactic radius. The presence of the signal in both samples, which have different typical ages, suggests that the warp is a gravitationally induced phenomenon.